Mn-induced strengthening hybridization effect of Co–O bond for stable oxygen evolution in acidic media. (1st February 2023) - Fan, Ruo-Yao; Zhao, Hui-Ying; Zhen, Yi-Nuo; Wang, Feng-Ge; Hu, Han; Chai, Yong-Ming; Dong, Bin
Graphical abstract: Highlights: Mn-induced can strengthen hybridization effect of Co-O bond of cobalt spinel oxide. Trace Mn in spinel oxide can effectively adjust the electronic structure of Co. Doped Mn can improve the intrinsic activity and stability of cobalt spinel oxide. Ligand confinement effect of CoBDC ensured the high dispersion and stability of active cobalt sites. Abstract: The development of transition metal-based acidic OER electrocatalyst is an important step to realize large-scale hydrogen production in low-cost proton exchange membrane (PEM) electrolytic cell. However, the current challenge is how to overcome the tendency of transition metal oxides dissolving in acidic environment to improve the long-term stability. Here, we prepared a trace amount of Mn-doped cobalt spinel oxide by simple room temperature ion exchange using a special Co-MOF precursor (CoBDC). Detailed physical characterizations combined with electrochemical tests showed that the introduction of infinitesimal Mn caused more particle cavities but did not destroy the crystal structure and intrinsic activity of cobalt spinel oxide. Due to the strengthening hybridization effect of Mn-induced Co-O bond, the stability of Mn0.08 -Co3 O4 -400 is 4–5 times higher than that of Co3 O4 -400 in strong acidic environment. In addition, the confinement effect of specific metal–organic coordination structure of CoBDC also ensured the dispersity and stability of the highly active cobalt sites. In brief, this work provides an effective strategy for the preparation of stable and efficient non-noble metal-base acidic OER electrocatalysts.